Correlation between symphyseal morphology and mandibular growth - Mahkameh Moshfeghi; Mahtab Nouri; Sanam Mirbeigi; Alireza Akbar Zadeh Baghban (Wolters Kluwer Medknow Publications, 2014)
Background: This study sought to assess symphyseal morphology in adolescents with different mandibular growth patterns (MGPs) in order to see if a relation exists. Materials and Methods: In this study the symphyseal parameters (height, depth, and ratio) of normal subjects were compared with four groups with malocclusion (cl III vertical, cl II vertical, cl III horizontal, and cl II horizontal). These groups (15 samples each) were matched (for sex and cervical maturation stage [CVMS]) based on their cephalograms and patient charts. Growth patterns were differentiated by seven vertical parameters and the Wylie analysis. After confirmation of normality of the groups and similarity of their variances the two-way analysis of variance (ANOVA) was used for analysis of data assessed by adjusted chi-square (P < 0.001). The comparison of cases with the normal group was performed by the Dunnett method. Intraclass Correlation Coefficient (ICC) was used for evaluation of intraobserver reliability. Results: We found the symphyseal ratio to have a significant correlation with the MGP (P < 0.001). The symphyseal ratio (Height/Depth) was small in a mandible with vertical growth pattern Cl II or Cl III. Conversely, a horizontal growth pattern of a Cl II or Cl III mandible was associated with a larger ratio of the symphysis in comparison with the normal group. The symphyseal ratio was also found to be greater in females. Conclusion: The symphyseal ratio was found to be strongly associated with the MGP.